Empagliflozin in Heart Failure with a Preserved Ejection Fraction - Anker, Stefan D; Butler, Javed; Filippatos, Gerasimos; Ferreira, João P; Bocchi, Edimar; Böhm, Michael; Brunner–La Rocca, Hans-Peter; Choi, Dong-Ju; Chopra, Vijay; Chuquiure-Valenzuela, Eduardo; Giannetti, Nadia; Gomez-Mesa, Juan Esteban; et al. (The New England journal of medicine, 2021)
In a randomized trial, 5988 patients with heart failure with preserved ejection fraction were assigned to receive either empagliflozin or placebo in addition to usual therapy. At a median of 26 months, the empagliflozin group had a lower incidence of cardiovascular death or hospitalization for heart failure than the placebo group.